Network analysis and tactical behaviour in soccer small-sided and conditioned games: influence of absolute and relative playing areas on different age categories. (2nd January 2020) - Moreira, Pedro Emílio Drumond; Barbosa, Gustavo Fernandes; Murta, Cristiano Da Conceição Ferreira; Pérez Morales, Juan Carlos; Bredt, Sarah Da Glória Teles; Praça, Gibson Moreira; Greco, Pablo Juan
ABSTRACT: This study aimed to compare the effect of manipulating the absolute and relative area of SSCG on players' behaviour. 36 players were selected from the U-13 and U-14 category. The SSCG were played in three different formats: 3 vs. 3 (36 × 27 m, 162 m 2 ), 3 vs. 3 + 1 (36 × 27 m, 139 m 2 ), and 3 vs. 3 + 1 large (40 × 29 m, 162 m 2 ). Tactical behaviour and network properties were assessed using the FUT-SAT and the Social Network Analysis, respectively. A two-way ANOVA was used to compare the dependent variables between the different SSCG and ages. Results showed that U-14 players performed more actions of offensive coverage (p = 0.01; small-to-medium effect) and presented a lower dispersion of the eigenvector centrality (p = 0.002; small effect). Moreover, increases in the relative playing area induced an increase of offensive coverage actions (p = 0.01; medium effect). The simultaneous reduction of absolute and relative playing area induced a higher frequency of offensive unity (p = 0.02; medium effect), increased the level of interaction between players (p = 0.001; large effect). We conclude that, for young players, U-13 and U-14 category, it is important to reduce the area of SSCG during training sessions to increase tactical performance.